A SUMO and ubiquitin code coordinates protein traffic at replication factories. (26th September 2016) - Lecona, Emilio; Fernandez‐Capetillo, Oscar
Abstract : Post‐translational modifications regulate each step of DNA replication to ensure the faithful transmission of genetic information. In this context, we recently showed that deubiquitination of SUMO2/3 and SUMOylated proteins by USP7 helps to create a SUMO‐rich and ubiquitin‐low environment around replisomes that is necessary to maintain the activity of replication forks and for new origin firing. We propose that a two‐flag system mediates the collective concentration of factors at sites of DNA replication, whereby SUMO and Ubiquitinated‐SUMO would constitute "stay" or "go" signals respectively for replisome and accessory factors. We here discuss the findings that led to this model, which have implications for the potential use of USP7 inhibitors as anticancer agents. Abstract : Collective post‐translational modification of proteins regulates the function of multi‐molecular machines. High levels of SUMO in the replisome preserves the integrity of the fork and acts as a signal to drive the ubiquitination of replication factors. We propose ubiquitin‐SUMO as a signal for the disassembly of the replisome upon termination.